1992
DOI: 10.1007/bf01839020
|View full text |Cite
|
Sign up to set email alerts
|

Controlling tick infestations and diseases in sheep by pour-on formulations of synthetic pyrethroids. A field study

Abstract: The use of synthetic pyrethroids in pour-on formulations reduced tick infestations and the incidence of tick-associated diseases in lambs more than dipping in organophosphate acaricides. Though the use of pyrethroids did not prevent the lambs from being infected with tick-borne fever (TBF), the incidence of lambs with lameness (tick pyaemia) or lambs suddenly found dead (Pasteurella haemolytica septicaemia), which often are seen in association with TBF, was reduced. The use of pyrethroids for three years did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…The present result is in accordance with earlier studies indicating that ticks can be found on animals already 13–14 days after treatment with either cypermethrin or deltamethrin [7,13]. An earlier field study also supports the present results, since most lambs seroconverted already three weeks after pyrethroid treatment [20]. The main reason for this lack of efficiency is unknown.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present result is in accordance with earlier studies indicating that ticks can be found on animals already 13–14 days after treatment with either cypermethrin or deltamethrin [7,13]. An earlier field study also supports the present results, since most lambs seroconverted already three weeks after pyrethroid treatment [20]. The main reason for this lack of efficiency is unknown.…”
Section: Discussionsupporting
confidence: 93%
“…However, acaricide treatment may reduce the losses due to secondary infections. For instance, the incidence of lambs with lameness (tick pyaemia) or sudden death ( Bibersteinia/Mannheimia septicaemia) has been reduced due to pour-on treatment [20]. The reason for this effect is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It also indicates that prophylactic treatment with acaricides does not prevent infection, as high seroprevalence of A. phagocytophilum was observed in flocks where lambs were treated with acaricides. It is previously shown that lambs treated with acaricides seroconvert after only 3 weeks on tick pasture [5,35]. Routine use of acaricides is not a sustainable measure due to the possibility of developing acaricide resistance [36-38].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier observations indicate that synthetical pyrethroids only give 2 to 3 weeks of full protection against ticks [ 18 , 12 ]. In addition, lambs grazing on tick pastures may seroconvert to E. phagocytophila after 3 weeks of tick exposure, although synthetical pyrethroids have been applied [ 11 ].…”
Section: Discussionmentioning
confidence: 99%